Transmitted Drug Resistance in Antiretroviral Therapy-Naive Persons With Acute/Early/Primary HIV Infection: A Systematic Review and Meta-Analysis - Guo, Chunxiang; Wu, Yaxin; Zhang, Yang; Liu, Xinchao; Li, Aixin; Gao, Meixia; Zhang, Tong; Wu, Hao; Chen, Guanzhi; Huang, Xiaojie (Frontiers in Pharmacology, 2021)
Background: The widespread use of antiretroviral therapy (ART) has raised concerns about the emergence of HIV transmitted drug resistance (TDR). Acute HIV infection (AHI) was the most appropriate time to detect the spread of TDR. In this meta-analysis, our purpose was to evaluate the level of TDR in ART-naive patients with primary HIV infection (PHI)/AHI/early HIV infection (EHI) and to describe the critical drug-resistant mutations. Methods: We systematically searched the literature between January 1, 2008, and April 30, 2021, in PubMed, Web of Science, Embase, and the Cochrane Library. To evaluate the overall prevalence of TDR, we extracted raw data and analyzed prevalence estimates using Stata SE. Results: The data of this meta-analysis come from 12 observational studies, covering 3,558 ART-naive individuals with PHI, AHI, or EHI. The overall prevalence of HIV-TDR is 9.3% (95% CI: 6.8%–11.8%, I2 = 81.1%, in 11 studies). The prevalence of resistance by drug class is the highest for the nonnucleoside reverse transcriptase inhibitors (NNRTIs) at 5.7% (95% CI: 2.9%–8.5%, I2 = 96.6%, in 11 studies), followed by nucleoside reverse transcriptase inhibitors (NRTIs) at 3.4% (95% CI: 1.8%–5.0%, I2 = 86.3%, in 10 studies) and protease inhibitors (PIs) at 3.3% (95% CI: 2.7%–3.9%, I2 = 15.6%, in 10 studies). The prevalence of TDR to integrase inhibitors (INIs) is 0.3% (95% CI: 0.1%–0.7%, I2 = 95.9%, in three studies), which is the lowest among all antiretroviral drugs. Conclusion: The overall prevalence of TDR is at a moderate level among AHI patients who have never received ART. This emphasizes the importance of baseline drug resistance testing for public health surveillance and guiding the choice of ART. In addition, the prevalence of TDR to NNRTIs is the highest, while the TDR to INIs is the lowest. This may guide the selection of clinical antiretroviral drugs.